2013
DOI: 10.1387/revpsicodidact.7909
|View full text |Cite
|
Sign up to set email alerts
|

Peer Victimization and Ethnic-Cultural Peer Victimization: Self-Esteem and School Relations between Different Cultural Groups of Students in Andalusia, Spain // Victimización étnico-cultural entre iguales: autoestima y relaciones en la escuela entre...

Abstract: ResumenLa finalidad de esta investigación es estudiar la victimización entre iguales (10 tipos) y la victimización étnico-cultural entre iguales (10 tipos), así como sus relaciones con la autoestima, ajuste social y número de amigos en la escuela, prestando especial atención a la variable cultural. Para ello una muestra representativa de estudiantes preadolescentes y adolescentes (edad media = 14.48 años) de la región de Andalucía (España) compuesta por 7.037 estudiantes culturalmente diversos (80.1% mayoritar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

8
29
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 34 publications
(39 citation statements)
references
References 31 publications
8
29
0
2
Order By: Relevance
“…Our findings reinforce the set of studies that have claimed adolescence to be critical for students' engagement in school (Darr, 2011;Marks, 2000;Rodríguez-Fernández et al, 2012;Rodríguez-Hidalgo, Ortega-Ruiz, & Zych, 2014;Wang & Holcombe, 2010). Cognitive and agency engagement seem to be devalued by peers and to be negatively associated with students' social standing (Preckel et al, 2013), suggesting that this decrease seems to be related to the changes that occur in peer influence, which significantly increases during adolescence, contrary to what occurs with family influence (Janosz et al, 2008;Li et al, 2011;Ryan, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…Our findings reinforce the set of studies that have claimed adolescence to be critical for students' engagement in school (Darr, 2011;Marks, 2000;Rodríguez-Fernández et al, 2012;Rodríguez-Hidalgo, Ortega-Ruiz, & Zych, 2014;Wang & Holcombe, 2010). Cognitive and agency engagement seem to be devalued by peers and to be negatively associated with students' social standing (Preckel et al, 2013), suggesting that this decrease seems to be related to the changes that occur in peer influence, which significantly increases during adolescence, contrary to what occurs with family influence (Janosz et al, 2008;Li et al, 2011;Ryan, 2001).…”
Section: Discussionsupporting
confidence: 87%
“…Several European studies have reported similar findings (Strohmeier, Kärnä, & Salmivalli, 2011;Strohmeier, Spiel, & Gradinger, 2008). However, some research within Europe has concluded that there are no significant differences in the prevalence of victimisation as a function of the cultural background of the participants (Fandrem, Strohmeier, & Roland, 2009;Monks, Ortega-Ruiz, & Rodríguez-Hidalgo, 2008;Rodríguez-Hidalgo, Ortega-Ruiz, & Zych, 2014;Sweeting & West, 2001).…”
mentioning
confidence: 77%
“…They argue that cultural victimisation can be carried out in a variety of ways, not only by racist insults, but also by other means such as social exclusion and the spreading of rumours, and that these forms of victimisation are experienced more often by individuals from cultural minority groups than those in the cultural majority (McKenney, Pepler, Craig, & Connolly, 2006;Monks et al, 2008;Rodríguez-Hidalgo et al, 2014;Verkuyten & Thijs, 2001, 2002. In this way, a victim of cultural victimisation may experience distinct types of racist aggression.…”
mentioning
confidence: 99%
“…Similarly, the social behavior of each individual is the result of the complex interaction of biological, psychological and social factors. There are studies analyzing social behavior and its relationship with variables such as parenting style (Fuentes, García, Gracia, & Alarcón, 2015), age, sex, motivational values and personality (Musitu, Moreno, & Murgui, 2007) and cultural facets (Rodríguez-Hidalgo, Ortega-Ruiz, & Zych, 2014). Behavior, conduct or attitudes influencing social adaptation have also been analyzed, concentrating on such aspects as empathy, interpersonal relations and social anxiety (Degnan, Almas, & Fox, 2010;Delgado, Inglés, & García-Fernández, 2013), differences between men and women (Crapanzano, Frick, Childs, & Terranova, 2011), etc. Returning to the relationship between attitudes and values noted by Hollander (1968), an example of the connection between interpersonal values and attitudes may be observed in an analysis of the victims of aggression, who acquire a negative view and unfavorable values, such as insecurity and feeling threatened by their surroundings (Sutton & Smith, 1999), becoming timid and anxious (Polo, León, Gómez, Palacios, & Fajardo, 2013), introverted (Oñate & Piñuel, 2005), and socially isolated (Moreno, Vacas & Roa, 2006).…”
Section: Introductionmentioning
confidence: 99%